2020
DOI: 10.18203/2349-3259.ijct20201712
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum osteocalcin levels and vitamin K status by daily cheese intake

Abstract: <p class="abstract"><strong>Background:</strong> Cheese is a major source of long-chained vitamin K2 variants. How intake of vitamin K2 rich cheese affects vitamin K and osteocalcin has not been studied. The aim was to establish a maximum efficacy dose (MED) after daily intake of vitamin K2-rich cheese (Jarlsberg<sup>®</sup>) based on increase in ratio between carboxylated and undercarboxylated osteocalcin during a five-week diet.</p><p class="abstract"><strong>M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 33 publications
(42 reference statements)
4
10
1
Order By: Relevance
“…The six week run-in periods with daily MED of Jarlsberg® preceding the de-escalation and maintenance studies verified the increases in tOC levels, osteocalcin ratio and serum vitamin K2 as previously reported. 12 The studies verified the increases in vitamin K status, measured as osteocalcin carboxylation, as well as serum vitamin K2. The obtained positive effects are not transient and can be retained by daily intake of Jarlsberg®.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The six week run-in periods with daily MED of Jarlsberg® preceding the de-escalation and maintenance studies verified the increases in tOC levels, osteocalcin ratio and serum vitamin K2 as previously reported. 12 The studies verified the increases in vitamin K status, measured as osteocalcin carboxylation, as well as serum vitamin K2. The obtained positive effects are not transient and can be retained by daily intake of Jarlsberg®.…”
Section: Discussionmentioning
confidence: 57%
“…In addition to the positive effect of daily Jarlsberg® cheese intake on tOC and the vitamin K2 variants, this previous study indicated a positive effect on the lipid patterns and blood pressure. 12 These findings and the known association between osteocalcin and health suggest that daily intake of vitamin K2 rich cheese may have a positive impact on public health. 5,6 In case the previous results can be verified in new clinical studies, a daily addition of cheese such as Jarlsberg® might be used as a prophylactic against several diseases and even as an addition to treatment of diseases like osteoporosis and hyperlipidaemia.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations